The Entrepreneur's Storytelling Who Revives from Failure: A Persuasive Analysis - Fahmi, Lukman; Nuryana, Amiatun (Proceedings of International Conference on Da'wa and Communication, 2021)
This study examines the persuasive techniques used in business storytelling of three entrepreneurs in Surabaya. They are Drs. Daryono, Abdul Chalim, and Samsudin. They experienced a slump in their first business history. Then they becomes a successful entrepreneur in their business until now. This studi applying descriptive qualitative methods. And this study finds that their business storytelling uses some of the seven components of the persuasive technique of Keraf with the use of different types. Drs. Daryono’s business storytelling use rationalization, identification, compensation, and projection. Abdul Chalim’s business storytelling use rationalization, identification, suggestion, and conformity. And Samsudin’s business storytelling use rationalization, identification, suggestion, conformity, compensation, and displacement.The persuasive techniques serve as promotional tools to persuade many schools and institutions persuade many people and make the business grow.